Glutathione Complexed Iron- Sulfur Centres. Reaction Intermediates and Evidence for a Template Effect Promoting Assembly and Stability - Qi, Wenbin (2013)
Assembly and stabilization of a glutathione-complexed [2Fe–2S] cluster is promoted by aggregation of glutathione. The cluster core selects the tetramer species from a collection of equilibrating solution aggregate species, and in turn the core is stabilized toward hydrolytic degradation. Studies of glutathione derivatives, in combination with mass spectrometric and Mo¨ssbauer investigations provide insight on reaction intermediates during formation of [2Fe–2S](GS)4